ANALISIS KEPUASAN MAHASISWA TERHADAP PENGGUNAAN APLIKASI EDLINK SEBAGAI MEDIA PEMBELAJARAN DI JURUSAN FARMASI POLTEKKES KEMENKES ACEH DENGAN MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) - Zaini, Rahmad; Wibawa, M Bayu; Yusian TB, Desita Ria (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2025)
Abstract— The advancement of educational technology demands effective use of online learning platforms such as Edlink, particularly in health education institutions. This study aims to analyze the satisfaction level of Pharmacy Department students at Poltekkes Kemenkes Aceh regarding the Edlink application using the End User Computing Satisfaction (EUCS) approach. A quantitative descriptive method was employed, with data collected through a Likert-scale questionnaire distributed to 79 randomly selected respondents. The analysis focused on five EUCS dimensions: content, accuracy, format, ease of use, and timeliness. Results show that 67.1% of respondents "agreed" and 12.7% "strongly agreed" with the overall quality of the application. The highest satisfaction was found in the ease of use and format dimensions, with 65.8% and 64.6% agreement respectively. Meanwhile, the accuracy and timeliness dimensions indicated minor dissatisfaction, with 2.5% of respondents disagreeing. This research contributes to the evaluation of Edlink services and offers recommendations for the development of LMS systems in health education settings. In conclusion, Edlink is considered adequate as a learning medium, though improvements are needed in timeliness and information accuracy. Further research is recommended to include other departments and explore the impact of satisfaction on learning outcomes.